Epoxy composite material as well as preparation method and application thereof

By filling aluminum oxide with magnetic particles in epoxy resin, an epoxy composite material with electrical insulation, electromagnetic shielding and thermal conductivity is prepared, which solves the problem that existing materials are difficult to have these properties at the same time, and achieves higher reliability Sex and flexibility.

CN119410102APending Publication Date: 2025-02-11SHENZHEN INST OF ADVANCED ELECTRONICS MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411552715.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When existing electronic packaging materials face high-density, highly integrated, 3D stacked electronic devices, it is difficult to have both electrical insulation, electromagnetic shielding and thermal conductivity, and traditional high-conductivity type electromagnetic shielding materials have a risk of short-circuit failure.

Method used

The epoxy composite material with aluminum oxide coated magnetic filler is prepared by liquid phase modification and high-temperature calcining method, and is highly filled into the epoxy resin, and obtained by thermal pressing and obtaining electrical insulation and electromagnetic Epoxy composite material with shielding and thermal conductivity.

Benefits of technology

It realizes that epoxy composite materials have high insulation, electromagnetic shielding and thermal conductivity in electronic packaging materials, reducing the risk of short-circuit failure and improving the reliability and flexibility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410102A_ABST
    Figure CN119410102A_ABST
Patent Text Reader

Abstract

The invention provides an epoxy composite material and a preparation method and application thereof, and the epoxy composite material is prepared from the following raw materials in parts by weight: 100 parts of modified magnetic particles; 5-16 parts of epoxy resin; 3-15 parts of a curing agent; the surfaces of the modified magnetic particles are provided with aluminum oxide coating layers. The preparation raw materials of the epoxy composite material provided by the invention comprise the modified magnetic particles with the aluminum oxide coating layers, and the modified magnetic particles are highly filled into the epoxy resin in a certain proportion, so that in the epoxy composite material, the insulating layer blocks a conductive seepage network, and meanwhile, the construction of a magnetic conduction path can be ensured; finally, the composite material has the effects of high insulativity and electromagnetic shielding at the same time, and the composite material also has relatively good heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic industry, and relates to an epoxy composite material and a preparation method and application thereof, and in particular to an electrical insulation-electromagnetic shielding-thermal conduction multifunctional epoxy composite material and a preparation method and application thereof. Background Art

[0002] As electronic devices develop towards miniaturization, high frequency and light weight, the rapid development of advanced electronic packaging has led to the construction of "chip high-rises" inside the devices: high density, high integration, and high reliability have gradually become urgent challenges facing electronic packaging materials. Under this high-density integrated packaging form, a more complex electromagnetic environment will be generated inside the chip, which will greatly increase the risk of electromagnetic interference to the chip. In the past few decades, the traditional electromagnetic shielding method mainly uses metal cavity structure, sputtered metal shielding structure or fractal shielding structure to achieve anti-electromagnetic interference protection for internal chips, but this method cannot meet the current electronic packaging development towards high density, high integration, and 3D stacking, and lacks flexibility in packaging form; in addition, the high conductivity of traditional shielding shells can easily cause short circuit failures inside the device and there are serious reliability problems. Later, researchers began to use carbon-based materials, metal particles, MXene and other materials to study new electromagnetic shielding materials, but they also rely on the intrinsic ultra-high conductivity of the material to achieve. Under the influence of these gradually mature theoretical knowledge and design ideas, people have gradually come to believe that electromagnetic shielding materials must have high conductivity, because all related reports know that their electromagnetic shielding effectiveness increases with the increase of conductivity. However, it is completely ignored that although the continuous increase in conductivity can indeed enhance the electromagnetic shielding performance, in fact, building a continuous and complete path inside the material is not a necessary condition for giving the material electromagnetic shielding performance. Considering that the primary goal of electronic packaging materials is to protect the safe and efficient operation of the internal chips, it is difficult to avoid the traditional high-conductivity type electromagnetic shielding materials in the face of the growing packaging needs. Always maintain high reliability, it is very likely to cause the risk of short circuit failure. This is often ignored in the design and development of electromagnetic shielding materials for early electronic packaging. This extremely critical engineering requirement.

[0003] Epoxy Molding Compound (EMC) is a commonly used semiconductor packaging material, usually used to encapsulate and protect chips, wafers and other microelectronic devices. It consists of an epoxy resin matrix, inorganic fillers and additives, has good electrical insulation, mechanical properties and chemical resistance, and can protect chips from humidity, corrosion and mechanical damage. At present, epoxy molding compounds are mainly composed of epoxy resin, curing agent, and filler (occupying the vast majority), among which epoxy resin as the matrix part has been widely recognized and used by the public due to its good chemical and mechanical properties, low water absorption, excellent wetting characteristics, good thermal stability and low cost. At present, traditional fillers usually use silica particles, alumina particles, aluminum nitride particles, etc. These particles are often characterized by high insulation, non-magnetic, and limited thermal conductivity, which makes epoxy composite materials completely unable to have electromagnetic shielding performance even at high filling content, and have limited thermal conductivity. In addition, although filling highly conductive particles in epoxy resin will have electromagnetic shielding properties under high filling, a conductive percolation network will be formed inside the resin, completely losing the most critical high insulation performance of the epoxy molding compound.

[0004] Therefore, in the art, it is desired to develop an epoxy composite material having electrical insulation, electromagnetic shielding, and thermal conductivity properties. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide an epoxy composite material and a preparation method and application thereof. The epoxy composite material provided by the present invention has electrical insulation, electromagnetic shielding, and thermal conductivity, and can be used as an epoxy molding compound in the field of electronic packaging materials. The epoxy composite material provided by the present invention is used in semiconductor packaging materials, which can integrate the electromagnetic shielding performance of the metal shielding shell and the electrical insulation performance of the epoxy molding compound, eliminating the need for an additional metal shielding shell. The schematic diagram of the application of the high conductive shielding layer and epoxy molding compound in the prior art in semiconductor packaging materials is shown in FIG. Figure 1A As shown, the schematic diagram of the application of the epoxy composite material provided by the present invention in semiconductor packaging materials is as follows Figure 1B shown.

[0006] Specifically, the present invention discloses a method for preparing a magnetic filler coated with alumina, and uses it for epoxy composite material filling. Under certain ratios and process optimization, the cured epoxy composite material is prepared by hot pressing. After a series of tests and verifications, the composite material has a high volume resistivity, certain electromagnetic shielding performance, and good thermal conductivity. The liquid phase coating process of the magnetic filler involves two parts: first, the alumina-coated magnetic particles are prepared by liquid phase modification and high-temperature calcination; second, the obtained particles are mixed evenly with epoxy resin as fillers at a certain ratio, and cured at a certain temperature to obtain the epoxy composite material; finally, the various functional characteristics of the epoxy composite material are determined by performance testing.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an epoxy composite material, wherein the raw materials for preparing the epoxy composite material include the following components in parts by weight:

[0009] 100 parts of modified magnetic particles;

[0010] Epoxy resin 5-16 parts;

[0011] 3-15 parts of curing agent;

[0012] The surface of the modified magnetic particles has an aluminum oxide coating layer.

[0013] The raw materials for preparing the epoxy composite material provided by the present invention include modified magnetic particles with an aluminum oxide coating layer, and the modified magnetic particles are highly filled into epoxy resin at a certain proportion. Inside the epoxy composite material, the insulating layer blocks the conductive percolation network while ensuring the construction of the magnetic conductive path, and finally the composite material can have the effects of high insulation and electromagnetic shielding at the same time, and the composite material also has good thermal conductivity.

[0014] In the present invention, the raw materials for preparing the epoxy composite material are measured in parts by weight. Based on 100 parts of the modified magnetic particles, the amount of epoxy resin can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, etc., and the amount of curing agent can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.

[0015] Preferably, the surface of the modified magnetic particles has any one of an amorphous aluminum oxide coating layer, a delta-aluminum oxide coating layer, a gamma-aluminum oxide coating layer, and an alpha-aluminum oxide coating layer. The present invention regulates the coating layer on the surface to a certain extent, and can realize the preparation of an epoxy composite material integrating electrical insulation, electromagnetic shielding, and thermal conductivity under different types of aluminum oxide.

[0016] Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, 3,4-epoxycyclohexylmethyl methacrylate, 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, 3,4-epoxycyclohexenemethyl-3,4-epoxycyclohexene ester, and 4-vinyl-1-cyclohexene diepoxide, or a combination of at least two thereof.

[0017] Preferably, the curing agent includes any one of diaminodiphenyl sulfone (DDS), diaminodiphenylmethane (DDM), 4,4'-methylenedianiline (MDA), metaphenylenediamine (MPDA), 4,4'-methylenebis(2-ethyl)aniline, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and dodecenylsuccinic anhydride, or a combination of at least two thereof.

[0018] Preferably, the raw materials for preparing the epoxy composite material further include 0.01-0.1 parts (eg, 0.01 parts, 0.03 parts, 0.05 parts, 0.08 parts, 0.1 parts, etc.) of catalyst.

[0019] Preferably, the catalyst comprises 2-methylimidazole.

[0020] In a second aspect, the present invention provides a method for preparing the epoxy composite material as described in the first aspect, the preparation method comprising the following steps:

[0021] Mixing the formulated amounts of epoxy resin, curing agent, and optional catalyst, and then adding the modified magnetic particles to obtain a mixture;

[0022] The mixture is hot-pressed to obtain the epoxy composite material.

[0023] Preferably, the mixing is carried out in a high-speed mixer.

[0024] Preferably, the temperature of the hot pressing is 150-220°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, etc.

[0025] Preferably, the hot pressing time is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.

[0026] Preferably, the hot pressing pressure is 5 to 20 MPa, for example, 5 MPa, 8 MPa, 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa, 20 MPa, etc.

[0027] Preferably, the modified magnetic particles are prepared by the following method:

[0028] The magnetic particles are added to an aqueous solution of aluminum nitrate, and then a buffer solution is added to adjust the pH value of the system to obtain a mixture;

[0029] The mixture is poured into a container with mechanical stirring, stirred, and reacted to prepare magnetic particles that are preliminarily modified by a liquid phase method;

[0030] The preliminarily modified magnetic particles are dried, calcined at high temperature, and ground to obtain the modified magnetic particles.

[0031] In view of the existing problems in this field, the present invention develops a method for preparing magnetic particles coated with alumina, and fills the magnetic particles into an epoxy system as a filler. The mutually exclusive relationship between insulation and electromagnetic shielding can be well balanced through process improvement and ratio optimization. Finally, a multifunctional electrical insulation-electromagnetic shielding-thermal conductive epoxy composite material is obtained through design optimization, and it is expected to be used as an epoxy molding compound in advanced packaging materials.

[0032] Preferably, the magnetic particles include any one of sendust particles, iron-nickel particles, ferrite particles, iron-nickel-molybdenum particles, iron-silicon particles, carbon-based iron particles, and iron powder, or a combination of at least two of them.

[0033] Preferably, the particle size of the magnetic particles is 5 to 75 μm, for example 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, etc.

[0034] Preferably, the magnetic particles further include the following pretreatment steps before use: washing, centrifugation, and drying.

[0035] Preferably, the washing comprises ultrasonic washing using an organic solvent.

[0036] Preferably, the organic solvent includes any one of anhydrous ethanol, acetone, ethylene glycol, and butanone.

[0037] Preferably, the drying temperature is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0038] Preferably, the molar concentration of the aluminum nitrate aqueous solution is 0.1-1 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc.

[0039] Preferably, the amount of 0.1-1 mol / L (e.g., 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc.) aluminum nitrate aqueous solution is 100 mL, and the amount of the magnetic particles is 10-20 g, e.g., 10 g, 12 g, 14 g, 15 g, 16 g, 18 g, 20 g, etc.

[0040] Preferably, the buffer comprises acetic acid-sodium acetate buffer.

[0041] Preferably, the molar concentration of the acetic acid-sodium acetate buffer is 0.1-2.0 mol / L, for example, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, etc.

[0042] Preferably, the pH value is 4 to 7, for example, 4, 4.5, 5, 5.5, 6, 6.5, 7, etc.

[0043] Preferably, the stirring speed is 150-500 rpm, for example, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.

[0044] Preferably, the stirring temperature is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc.

[0045] Preferably, the stirring time is 2 to 96 hours, for example, 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours, 48 ​​hours, 60 hours, 72 hours, 84 hours, 96 hours, etc.

[0046] Preferably, the reaction is carried out in a light-proof, sealed environment.

[0047] Preferably, the drying temperature is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.

[0048] Preferably, the high temperature calcination temperature is 450-1300°C, for example, 450°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, etc.

[0049] Preferably, the high temperature calcination time is 0.5 to 3.5 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, etc.

[0050] The preparation method of modified magnetic particles provided by the present invention can obtain modified magnetic particles with different coating layer types under different calcination temperatures and times: amorphous alumina-coated modified magnetic particles, δ-alumina-coated modified magnetic particles, γ-alumina-coated modified magnetic particles, and α-alumina-coated modified magnetic particles, etc.

[0051] Preferably, the high-temperature calcination is carried out in a tubular furnace protected by an inert gas.

[0052] Preferably, the inert gas comprises argon.

[0053] Preferably, the particle size of the modified magnetic particles is 5 to 75 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, etc.

[0054] As a preferred technical solution of the present invention, the modified magnetic particles are prepared by the following method:

[0055] The magnetic particles are ultrasonically washed with an organic solvent, centrifuged, and repeated three times, and then dried to obtain clean magnetic particles; the clean magnetic particles are added to an aqueous solution of aluminum nitrate with a molar concentration of 0.1 to 1 mol / L, and then an acetic acid-sodium acetate buffer with a molar concentration of 0.1 to 2 mol / L is added, and the pH value of the system is adjusted to 4 to 6 to obtain a mixture;

[0056] The mixture is poured into a container with mechanical stirring, placed in an oil bath in a light-proof and sealed environment, and stirred and reacted at 60 to 90° C. for 2 to 96 hours to prepare magnetic particles that are preliminarily modified by a liquid phase method;

[0057] The magnetic particles after the preliminary modification are taken out and dried at 60-100° C., placed in a tube furnace protected by argon gas and calcined at 450-1300° C. for 0.5-3.5 hours, and finally ground to obtain modified magnetic particles with an inorganic alumina coating layer. Grinding can reduce the agglomeration of the modified magnetic particles and ensure that they have good dispersibility in the composite material.

[0058] The present invention blocks the conductive path by coating an aluminum oxide layer on the surface of a high-magnetic conductive filler through liquid phase modification and high-temperature calcination. The aluminum oxide layer satisfies high insulation. At the same time, the crystal form of the aluminum oxide coating layer on the surface of the filler can be reasonably adjusted by adjusting the temperature of the high-temperature calcination, and then mixed with epoxy resin and curing agent in a certain proportion for hot pressing to finally obtain an epoxy composite material with integrated electrical insulation, electromagnetic shielding and thermal conductivity. The magnetic filler with an insulating coating layer can ensure the high volume resistivity of the overall epoxy composite material because the percolation network is blocked inside the composite material. However, the insulating coating layer does not form a magnetic domain wall at a suitable thickness to affect the formation of the magnetic conductive path. Under this reasonable material design, the epoxy composite material will have electromagnetic shielding performance. This is different from the electromagnetic shielding method of conventional conductive materials. The epoxy composite material mainly produces electromagnetic shielding effectiveness through the synergistic mechanism of local eddy current loss, magnetic loss and interface loss. The preparation method of the present invention is simple and the equipment requirements are relatively low. The prepared epoxy composite material can have excellent electromagnetic shielding performance and thermal conductivity under the condition of maintaining high insulation, and is expected to be used in the field of electronic packaging as a new advanced packaging material.

[0059] In a third aspect, the present invention provides a use of the epoxy composite material as described in the first aspect in semiconductor packaging.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] (1) The raw materials for preparing the epoxy composite material provided by the present invention include modified magnetic particles with an aluminum oxide coating layer, and the modified magnetic particles are highly filled into epoxy resin at a certain ratio. Inside the epoxy composite material, the insulating layer blocks the conductive percolation network while ensuring the construction of the magnetic conductive path, and finally the composite material can have the effects of high insulation and electromagnetic shielding, and the composite material also has good thermal conductivity.

[0062] (2) The epoxy composite material provided by the present invention is used for epoxy molding compound, which can integrate the electromagnetic shielding performance of the metal shielding shell and the electrical insulation performance of the epoxy molding compound, thereby eliminating the additional metal shielding shell preparation process.

[0063] (3) The epoxy composite material provided by the present invention has higher reliability in the field of advanced electronic packaging and can reduce the risk of short circuits. Since it has electrical insulation, electromagnetic shielding, and thermal conductivity, it has broader application prospects. At the same time, it also greatly increases the flexibility in advanced packaging design and no longer uses high conductivity as the only criterion for electromagnetic shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1A The diagram is a schematic diagram of the application of a high-conductivity shielding layer and epoxy molding compound in semiconductor packaging materials in the prior art.

[0065] Figure 1B This is a schematic diagram of the application of the epoxy composite material provided by the present invention in semiconductor packaging materials.

[0066] Figure 2 This is a SEM image of the Sendust particles used in the preparation example of the present invention.

[0067] Figure 3 SEM images (a, b) of the modified Sendust particles with an amorphous alumina coating layer provided in Preparation Example 1 of the present invention and SEM images (c, d) of the modified Sendust particles with an α-alumina coating layer provided in Preparation Example 2.

[0068] Figure 4 The XRD diagram (a) of the uncoated Sendust particles used in the preparation examples of the present invention, the XRD diagram (b) of the modified Sendust particles with an amorphous alumina coating layer provided in Preparation Example 1, and the XRD diagram (c) of the modified Sendust particles with an α-alumina coating layer provided in Preparation Example 2.

[0069] Figure 5 The SEM images of the epoxy composite materials provided in Comparative Example 3, Comparative Example 1, Example 2 and Example 1 of the present invention correspond to (a-d), respectively.

[0070] Figure 6 The cross section of the epoxy composite material provided in Example 1 of the present invention is polished after grinding, and the element distribution spectrum (EDS, corresponding to the elements in the upper left corner) of the magnetic particles after the aluminum oxide coating layer is modified.

[0071] Figure 7 A local enlarged view of the element distribution spectrum (EDS, corresponding to the elements in the upper left corner) of the magnetic particles after the alumina coating layer is modified after the cross section of the epoxy composite material provided in Example 1 of the present invention is ground and polished. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Preparation Example 1

[0074] In this preparation example, a modified magnetic particle is provided, and the preparation method comprises the following steps:

[0075] First, 15 g of sendust particles (particle size of 20 μm) were ultrasonically washed with anhydrous ethanol, centrifuged, repeated three times, and then dried at 80°C to obtain washed sendust particles; secondly, the washed sendust particles were added to 100 mL of 0.6 mol / L aluminum nitrate aqueous solution, and then 0.6 mol / L acetic acid-sodium acetate buffer was added to adjust the pH to 5; the solution was poured into a mechanical stirring container, placed in an oil bath in a light-proof and sealed environment, and stirred at 80°C for 48 hours to prepare sendust particles preliminarily modified by a liquid phase method; finally, the sendust particles were taken out and dried at 70°C, placed in a tubular furnace protected by argon gas, and calcined at 700°C for 1 hour, and then ground to obtain modified sendust particles (particle size of 20 μm) with an amorphous aluminum oxide coating layer.

[0076] Preparation Example 2

[0077] In this preparation example, a modified magnetic particle is provided, and the preparation method comprises the following steps:

[0078] First, 15 g of sendust particles (particle size of 20 μm) were ultrasonically washed with anhydrous ethanol, centrifuged, repeated three times, and then dried at 80°C to obtain washed sendust particles; secondly, the washed sendust particles were added to 100 mL of 0.6 mol / L aluminum nitrate aqueous solution, and then 0.6 mol / L acetic acid-sodium acetate buffer was added to adjust the pH to 5; the solution was poured into a mechanical stirring container, placed in an oil bath in a light-proof and sealed environment, and stirred at 80°C for 48 hours to prepare sendust particles preliminarily modified by a liquid phase method; finally, the sendust particles were taken out and dried at 70°C, placed in a tubular furnace protected by argon gas, and calcined at 1100°C for 1 hour, and then ground to obtain modified sendust particles (particle size of 20 μm) with an α-alumina coating layer.

[0079] Preparation Example 3

[0080] The only difference between this preparation example and preparation example 1 is that the concentration of the aluminum nitrate aqueous solution is 0.9 mol / L.

[0081] Comparative Preparation Example 1

[0082] In this comparative preparation example, a magnetic particle is provided, and the preparation method comprises the following steps:

[0083] First, 15 g of Sendust particles (particle size of 20 μm) were ultrasonically washed with anhydrous ethanol, centrifuged, and repeated three times, and then dried at 80°C to obtain clean Sendust particles; then, they were placed in a tubular furnace protected by argon and calcined at 700°C for 1 hour, and then ground to obtain unmodified Sendust particles (particle size of 20 μm).

[0084] The SEM image of the iron silicon aluminum particles used in the preparation example of the present invention is as follows Figure 2 shown.

[0085] The SEM images (a, b) of the modified sendust particles with an amorphous aluminum oxide coating layer provided in Preparation Example 1 of the present invention and the SEM images (c, d) of the modified sendust particles with an α-aluminum oxide coating layer provided in Preparation Example 2 are as shown in FIG. Figure 3 shown.

[0086] from Figure 2 and Figure 3 It can be seen that before modification, the surface of the Sendust particles is relatively smooth, and after modification, the surface of the Sendust particles becomes rough, and has a coating layer on the surface.

[0087] The XRD pattern (a) of the uncoated sendust particles used in the preparation examples of the present invention, the XRD pattern (b) of the modified sendust particles with an amorphous alumina coating layer provided in Preparation Example 1, and the XRD pattern (c) of the modified sendust particles with an α-alumina coating layer provided in Preparation Example 2 are shown in FIG. Figure 4 As shown, it can be seen that the present invention successfully synthesized modified Sendust particles with an amorphous aluminum oxide coating layer and modified Sendust particles with an α-aluminum oxide coating layer.

[0088] Example 1

[0089] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0090] 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin, methylhexahydrophthalic anhydride curing agent, and 2-methylimidazole catalyst were weighed and mixed, and then placed in a high-speed mixer for thorough mixing; then the modified magnetic particles obtained in Preparation Example 1 were added, and the mixture was mixed again to obtain a mixture; the mixture was placed in a mold coated with a release agent, and cured in a hot press at a temperature of 200° C. and a pressure of 15 MPa for 2.0 hours to obtain a cured epoxy composite material;

[0091] Among them, the mass ratio of modified magnetic particles, epoxy resin, curing agent and catalyst is 100:5.0:6.1:0.05.

[0092] Example 2

[0093] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0094] 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin, methylhexahydrophthalic anhydride curing agent, and 2-methylimidazole catalyst were weighed and mixed, and then placed in a high-speed mixer for thorough mixing; then the modified magnetic particles obtained in Preparation Example 1 were added, and the mixture was mixed again to obtain a mixture; the mixture was placed in a mold coated with a release agent, and cured in a hot press at a temperature of 200° C. and a pressure of 15 MPa for 2.0 hours to obtain a cured epoxy composite material;

[0095] Among them, the mass ratio of modified magnetic particles, epoxy resin, curing agent and catalyst is 100:11.3:13.7:0.05.

[0096] Example 3

[0097] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0098] Weigh and mix bisphenol A epoxy resin (E51) and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the modified magnetic particles obtained in Preparation Example 1, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 165° C. and a pressure of 15 MPa for 2.0 hours to finally obtain a cured epoxy composite material;

[0099] Among them, the mass ratio of modified magnetic particles, epoxy resin and curing agent is 100:7.0:4.2.

[0100] Example 4

[0101] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0102] Weigh and mix 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the modified magnetic particles obtained in Preparation Example 1, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 180° C. and a pressure of 15 MPa for 2.0 hours to finally obtain a cured epoxy composite material;

[0103] Among them, the mass ratio of modified magnetic particles, epoxy resin and curing agent is 100:6.7:4.4.

[0104] Example 5

[0105] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0106] Weigh and mix 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the modified magnetic particles obtained in Preparation Example 1, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 180° C. and a pressure of 15 MPa for 2.0 hours to obtain a cured epoxy composite material;

[0107] Among them, the mass ratio of modified magnetic particles, epoxy resin and curing agent is 100:15.1:10.0.

[0108] Example 6

[0109] In this embodiment, an epoxy composite material is provided, and a preparation method thereof comprises the following steps:

[0110] Weigh and mix 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the modified magnetic particles obtained in Preparation Example 2, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 180° C. and a pressure of 15 MPa for 2.0 hours to obtain a cured epoxy composite material;

[0111] Among them, the mass ratio of modified magnetic particles, epoxy resin and curing agent is 100:6.7:4.4.

[0112] Example 7

[0113] The only difference between this embodiment and embodiment 4 is that the modified magnetic particles are replaced by the modified magnetic particles obtained in preparation example 3 of equal weight.

[0114] Comparative Example 1

[0115] In this comparative example, an epoxy composite material is provided, and the preparation method comprises the following steps:

[0116] 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin, methylhexahydrophthalic anhydride curing agent, and 2-methylimidazole catalyst were weighed and mixed, and then put into a high-speed mixer to be fully mixed; then the unmodified magnetic particles obtained in Comparative Preparation Example 1 were added, and mixed again to obtain a mixture; the mixture was put into a mold coated with a release agent, and cured and molded in a hot press at a temperature of 200° C. and a pressure of 15 MPa for 2.0 hours to finally obtain a cured epoxy composite material;

[0117] Among them, the mass ratio of unmodified magnetic particles, epoxy resin, curing agent and catalyst is 100:5.0:6.1:0.05.

[0118] Comparative Example 2

[0119] In this comparative example, an epoxy composite material is provided, and the preparation method comprises the following steps:

[0120] Weigh and mix 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the unmodified magnetic particles obtained in Comparative Preparation Example 1, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 180° C. and a pressure of 15 MPa for 2.0 hours to finally obtain a cured epoxy composite material;

[0121] Among them, the mass ratio of unmodified magnetic particles, epoxy resin and curing agent is 100:6.7:4.4.

[0122] Comparative Example 3

[0123] In this comparative example, an epoxy composite material is provided, and the preparation method comprises the following steps:

[0124] Weigh and mix 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline epoxy resin and 4,4'-methylenebis(2-ethyl)aniline curing agent, put them into a high-speed mixer and mix them thoroughly; then add the unmodified magnetic particles obtained in Comparative Preparation Example 1, mix them again to obtain a mixture; put the mixture into a mold coated with a release agent, and cure it in a hot press at a temperature of 180° C. and a pressure of 15 MPa for 2.0 hours to finally obtain a cured epoxy composite material;

[0125] Among them, the mass ratio of unmodified magnetic particles, epoxy resin and curing agent is 100:15.1:10.0.

[0126] The SEM images of the epoxy composite materials provided in Comparative Example 3, Comparative Example 1, Example 2 and Example 1 of the present invention are as follows: Figure 5 As shown, they correspond to (a~d) respectively.

[0127] After the cross section of the epoxy composite material provided in Example 1 of the present invention is polished, the element distribution spectrum (EDS, corresponding to the element in the upper left corner) of the magnetic particles after the aluminum oxide coating layer is modified is as follows: Figure 6 shown.

[0128] After the cross section of the epoxy composite material provided in Example 1 of the present invention is polished, a local enlarged view of the element distribution spectrum (EDS, corresponding to the element in the upper left corner) of the magnetic particles after the aluminum oxide coating layer is modified is shown as follows: Figure 7 shown.

[0129] The epoxy composite materials provided in the examples and comparative examples were tested for performance, and the testing method was as follows:

[0130] (1) Electromagnetic shielding performance test: A vector network analyzer was used to test the frequency band X-band (8.2 GHz-12.4 GHz) at room temperature 25°C to test the prepared epoxy composite material with a size of 22.80 mm*10.15 mm*2.00 mm.

[0131] (2) Insulation performance test: Use a high resistance meter to test the volume resistivity of the sample at room temperature 25°C.

[0132] (3) Thermal expansion coefficient test: The sample was heated from room temperature to about 300°C at a heating rate of 5°C / min using a thermomechanical analyzer. The value calculated from the slope of the curve before the glass transition temperature of the sample is called CTE1. The value calculated from the slope of the curve after the glass transition temperature of the sample is called CTE2.

[0133] (4) Thermal conductivity test: The thermal diffusion coefficient α was obtained by using a laser flash thermal conductivity meter at room temperature of 25°C; the specific heat capacity parameter C was measured by using a differential scanning calorimeter at room temperature of 25°C p , heating rate 10℃ / min; density parameter ρ of the sample at room temperature 25℃ was measured using a density balance; finally, thermal conductivity k was calculated according to the formula: k=α·ρ·C p Calculated.

[0134] (5) Glass transition temperature: The sample was heated from 40°C to about 300°C at a heating rate of 10°C / min using a differential scanning calorimeter. The glass transition temperature was obtained based on the sudden turning point.

[0135] The performance test results are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] It can be seen from Table 1 that the epoxy composite materials provided by the embodiments of the present invention have excellent insulation properties (4.9E13~2.5E15Ω·cm) by changing the types of epoxy resin and curing agent, adding modified magnetic particles containing different types of aluminum oxide coating layers, and changing the ratio of each preparation raw material, and their electromagnetic shielding performance (15~25dB) and thermal conductivity (thermal conductivity: 0.95~3.45W / m·K)) can meet the requirements in electronic packaging materials.

[0140] Compared with Example 1, the insulating performance of the epoxy composite material provided in Comparative Example 1 is greatly reduced, and compared with Example 4, the insulating performance of the epoxy composite material provided in Comparative Example 2 is greatly reduced; compared with Example 5, the insulating performance of the epoxy composite material provided in Comparative Example 3 is greatly reduced; the insulating performance of the epoxy composite materials provided in Comparative Examples 1-3 cannot meet the requirements in electronic packaging materials.

[0141] The applicant declares that the present invention illustrates the epoxy composite material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An epoxy composite material, characterized in that: The raw materials for preparing the epoxy composite material include the following components in parts by weight: 100 parts of modified magnetic particles; Epoxy resin 5-16 parts; 3-15 parts of curing agent; The surface of the modified magnetic particles has an aluminum oxide coating layer.

2. The epoxy composite material according to claim 1, characterized in that: The surface of the modified magnetic particles has any one of an amorphous aluminum oxide coating layer, a delta-aluminum oxide coating layer, a gamma-aluminum oxide coating layer, and an alpha-aluminum oxide coating layer.

3. The epoxy composite material according to claim 1 or 2, characterized in that: The epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, 4-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, 3,4-epoxycyclohexylmethyl methacrylate, 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, 3,4-epoxycyclohexenemethyl-3,4-epoxycyclohexene ester, and 4-vinyl-1-cyclohexene diepoxide, or a combination of at least two thereof; Preferably, the curing agent includes any one of diaminodiphenyl sulfone, diaminodiphenylmethane, 4,4'-methylenedianiline, m-phenylenediamine, 4,4'-methylenebis(2-ethyl)aniline, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and dodecenylsuccinic anhydride, or a combination of at least two thereof.

4. The epoxy composite material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the epoxy composite material also include 0.01-0.1 parts of a catalyst; Preferably, the catalyst comprises 2-methylimidazole.

5. A method for preparing the epoxy composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Mixing the formulated amounts of epoxy resin, curing agent, and optional catalyst, and then adding the modified magnetic particles to obtain a mixture; The mixture is hot-pressed to obtain the epoxy composite material.

6. The preparation method according to claim 5, characterized in that: The mixing is carried out in a high-speed mixer; Preferably, the temperature of the hot pressing is 150-220°C; Preferably, the heat pressing time is 1 to 5 hours; Preferably, the hot pressing pressure is 5 to 20 MPa; Preferably, the modified magnetic particles are prepared by the following method: Adding magnetic particles to an aqueous solution of aluminum nitrate, then adding a buffer solution, and adjusting the pH value of the system to obtain a mixture; The mixture is poured into a container with a mechanical stirrer, stirred, and reacted to prepare magnetic particles that are preliminarily modified by a liquid phase method; The preliminarily modified magnetic particles are dried, calcined at high temperature, and ground to obtain the modified magnetic particles.

7. The preparation method according to claim 6, characterized in that: The magnetic particles include any one of sendust particles, iron-nickel particles, ferrite particles, iron-nickel-molybdenum particles, iron-silicon particles, carbon-based iron particles, and iron powder, or a combination of at least two thereof; Preferably, the particle size of the magnetic particles is 5 to 75 μm; Preferably, the magnetic particles further include the following pretreatment steps before use: washing, centrifugation, and drying; Preferably, the washing comprises ultrasonic washing with an organic solvent; Preferably, the organic solvent includes any one of anhydrous ethanol, acetone, ethylene glycol, and butanone; Preferably, the drying temperature is 60-80°C; Preferably, the molar concentration of the aluminum nitrate aqueous solution is 0.1 to 1 mol / L; Preferably, the amount of 0.1-1 mol / L aluminum nitrate aqueous solution is 100 mL, and the amount of the magnetic particles is 10-20 g; Preferably, the buffer comprises acetic acid-sodium acetate buffer; Preferably, the molar concentration of the acetic acid-sodium acetate buffer is 0.1 to 2.0 mol / L; Preferably, the pH value is 4-7.

8. The preparation method according to claim 6 or 7, characterized in that: The stirring speed is 150-500 rpm; Preferably, the stirring temperature is 60 to 90°C; Preferably, the stirring time is 2 to 96 hours; Preferably, the reaction is carried out in a light-proof, sealed environment.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The drying temperature is 60-100°C; Preferably, the high temperature calcination temperature is 450-1300°C; Preferably, the high temperature calcination time is 0.5 to 3.5 hours; Preferably, the high-temperature calcination is carried out in a tubular furnace protected by an inert gas; Preferably, the inert gas comprises argon; Preferably, the particle size of the modified magnetic particles is 5 to 75 μm.

10. Use of the epoxy composite material according to any one of claims 1 to 4 in semiconductor packaging.

Citation Information

Patent Citations

  • Method for coating surface of metal soft magnetic powder in situ with Al2O3 insulating layer

    CN108597711A

  • Composition for complex sheet, complex sheet comprising the same, and preparation method of the complex sheet

    KR1020150052591A

  • Epoxy resin composition used for encapsulating semiconductor and semiconductor device using the composition

    US20030024723A1